Good enough to eat! food presentation and service - Verso, Nicholas; Rutigliano, Katrina; Films For The Humanities & Sciences (Firm).; Video Education Australasia (Australia : VEA, 2010)
'If food looks good, we are more or less compelled to find out if it tastes good. This program explores the way food is styled and presented and how those aesthetic decisions shape the overall experience of a meal-whether at home or in a restaurant. Taking into account the human body's five senses, the video demonstrates how we evaluate food and addresses the sense-related characteristics that people look for in a variety of meals. Interviews with a chef, a nutritionist, and a food stylist reveal the many ways in which food can be presented, from small parties to banquets.'--Container.
Directors of photography, Charlie Sarroff, Ben Milward-Bason.
Presenter: Cassidy Gregory-Heydon.
DVD format.
Keywords: Food services